Terror in post 9/11 art: The 9/11 attacks as inspiration for arte and cinema - Iturriaga Barco, Diego; Moreno Galilea, Diego; Quintero González, Francisco (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
September 11, 2001 was one of the most tragic days in recent human history. A terrorist attack put the entire Western society in check, showing an enormous force and destroying the lives of thousands of free citizens. Conspiracy is one of the most widespread theories to explain the origin of these attacks, but also money, religion and power. With almost 3,000 murdered and numerous unidentified human remains, the main documents remain undeclassified by the US administration, after having passed four different presidents, both Republicans and Democrats.